2014
DOI: 10.1002/2013ja019044
|View full text |Cite
|
Sign up to set email alerts
|

NOx production due to energetic particle precipitation in the MLT region: Results from ion chemistry model studies

Abstract: Production of neutral species such as NO x (N, NO, and NO 2 ) during particle-induced ionization events plays an important role in the chemistry of the mesosphere and lower thermosphere (MLT) region, especially in high latitudes. The effective production rate of NO x is composed of the direct production in reactions associated with the ionization or dissociation process and of indirect production during subsequent ionic reactions and recombination. A state of the art ion chemistry model is used to study the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…RAD/RAD-FUBRAD (Dietmüller et al, 2016) provides the parameterization of radiative transfer based on Fouquart and Bonnel (1980) and Roeckner et al (2003) (RAD). For a better resolution of the UV-VIS spectral band, RAD-FUBRAD is used for pressures lower than 70 hPa, increasing the spectral resolution in the UV-VIS from 1 band to 106 bands (Nissen et al, 2007;Kunze et al, 2014). Table 3 presents more details of the SW radiation and photolysis schemes in comparison to WACCM.…”
Section: Chemistry-climate Model Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…RAD/RAD-FUBRAD (Dietmüller et al, 2016) provides the parameterization of radiative transfer based on Fouquart and Bonnel (1980) and Roeckner et al (2003) (RAD). For a better resolution of the UV-VIS spectral band, RAD-FUBRAD is used for pressures lower than 70 hPa, increasing the spectral resolution in the UV-VIS from 1 band to 106 bands (Nissen et al, 2007;Kunze et al, 2014). Table 3 presents more details of the SW radiation and photolysis schemes in comparison to WACCM.…”
Section: Chemistry-climate Model Descriptionsmentioning
confidence: 99%
“…HO x production per ion pair as a function of altitude and ion pair production rate (IPR). Verronen and Lehmann, 2013;Nieder et al, 2014) is encouraged. Similarly, if atmospheric models include detailed cluster ion chemistry of the lower ionosphere (D region), then the ionization rates should be used to drive the production rates of the primary ions (N + 2 , N + , O + 2 , O + ) and neutrals (N, O) produced in particle impact ionization or dissociation (Sinnhuber et al, 2012).…”
Section: Appendix C: Recommendations For Geographic Projection Of Iprmentioning
confidence: 99%
“…EUV photoionization rates are calculated based on the parameterization of Solomon and Qian (2005). Ionic reactions are not included in the chemistry scheme, but the production of odd nitrogen species as a function of ionization rates and atmospheric state is calculated using the parameterization of Nieder et al (2014), adapted for photoionization by implementing a dependency on the primary ion composition. The production of HO x is considered using the parameterization of (Solomon et al, 1981), an approach which is widely used and has been validated both in comparison to observations of ozone loss, and in comparison to ion chemistry model results; see, e.g., Funke et al (2011); M. Sinnhuber et al (2012).…”
Section: Dctmmentioning
confidence: 99%
“…More complex ion-chemistry models such as the Sodankyla or University of Bremen models (e.g. Verronen et al, 2002;Nieder et al, 2014) use large numbers of individual ion species (up to 55 positive ions, 49 negative ions) with the aim of calculating both electron and individual ion densities and production rates of neutral trace constituents. As demonstrated by the comparisons cited above, this level of complexity is not needed to estimate electron density.…”
Section: Ion and No Production Rate Modelmentioning
confidence: 99%
“…Our model does not provide a direct calculation of the production of NO. Recent work using the University of Bremen model (Nieder et al, 2014) has shown that NO x production rates should be about 1.25 times the ion production rate below 80 km, increasing to about 1.7 times as height increases up to 110 km, with the ratio of NO / NO x about 0.55 below 110 km. However, the partitioning depends on conditions so here we estimate an "upper limit" NO production rate from the total ionization rate by multiplying by a factor of 1.25, while noting that this may still be an underestimate by up to 35 % between 80 and 110 km.…”
Section: Ion and No Production Rate Modelmentioning
confidence: 99%